Analysis of mortality due to communicable and maternal and child diseases: an ecological study based on worldwide data (Research, Society and Development, 2023)
Objective: to assess the prevalence of mortality from communicable and maternal and children diseases in different countries and world regions, comparing with the population < 14 years, per capita income, Human Capital Index (HCI) and basic sanitation. Methods: observational study of the ecological type. Data collection was carried out through the World Bank Group, where information from 266 world regions and countries was extracted in 2019, except for the HCI (2020). Bivariate and multivariate analysis was performed using linear progression, with the outcome being the prevalence of mortality from communicable and maternal-children diseases. Results: The results obtained showed a negative correlation for per capita income, HCI and basic sanitation, in a proportion of decrease in mortality of 0,05%, 11,1% and 0,4%, respectively. Age